34. x - 3 = 8x + 4
-3 - 4 = 8x - x
-7 = 7x
-7/7 = x
-1 = x
y = x - 3
y = -1 - 3
y = -4
solution is (-1,-4)
===================
35. -6 = -x - 2y
x = -2y + 6
2 + 5x = -2y
2 + 5(-2y + 6) = -2y
2 - 10y + 30 = -2y
32 = -2y + 10y
32 = 8y
32/8 = y
4 = y
2 + 5x = -2y
2 + 5x = -2(4)
2 + 5x = -8
5x = -8 - 2
5x = -10
x = -10/5
x = -2
solution is (-2,4)
==================
36. 4x + 6y = 2000
x + y = 410
==================
37. 4x + 6y = 2000
x + y = 410......multiply by -6
----------------------
4x + 6y = 2000
-6x - 6y = - 2460 (result of multiplying by -6)
--------------------add
-2x = - 460
x = -460/-2
x = 230 <=== tickets in advance
5.3/8.8=x/14.3
AB is x,
x= 2.43
Hope I helped.
Answer:
Step-by-step explanation:
1) the triangle is a right angle triangle.
From the given right angle triangle,
With 67° as the reference angle,
x represents the adjacent side of the right angle triangle.
17 represents the opposite side of the right angle triangle.
To determine x, we would apply
the Tangent trigonometric ratio.
Tan θ = opposite side/adjacent side.
Therefore,
Tan 67 = 17/x
xTan 67 = 17
x = 17/Tan 67
x = 17/2.3559
x = 7.22
2) From the given right angle triangle, with 24° as the reference angle,
x represents the opposite side of the right angle triangle.
12 represents the adjacent side of the right angle triangle.
To determine x, we would apply
the Tangent trigonometric ratio.
Tan θ = opposite side/adjacent side.
Therefore,
Tan 24 = x/12
x = 12Tan 24
x = 12 × 0.4452
x = 5.34